2002
DOI: 10.1080/07399330290107313
|View full text |Cite
|
Sign up to set email alerts
|

Women's Reflections on Divorce-- 10 Years Later

Abstract: Ten years after divorce 95 women who participated in an earlier study of divorce were asked to reflect on their lives since their divorce. They were mailed a questionnaire to describe demographic data, self-esteem, control, life assessment, and their lives since divorce. Fewer than half remarried and of those who did, 10 divorced a second time. Slightly more women partnered than married. Their overall assessment of their lives was reported positively. However, 25% felt the same or worse than they had 10 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Adults have more trouble adjusting to divorce if they have less income (Amato, 2000; Booth & Amato, 1991; Duffy, Thomas, & Trayner, 2002). Extending this finding to children of divorce, one might expect that children from families with higher incomes prior to the divorce would be less affected by their parents’ separation than children whose families had fewer monetary resources, because they would be less likely to experience stresses from poor housing, education, neighborhoods, and communities.…”
Section: Moderating the Effects Of Divorce: Risk And Protective Factorsmentioning
confidence: 99%
“…Adults have more trouble adjusting to divorce if they have less income (Amato, 2000; Booth & Amato, 1991; Duffy, Thomas, & Trayner, 2002). Extending this finding to children of divorce, one might expect that children from families with higher incomes prior to the divorce would be less affected by their parents’ separation than children whose families had fewer monetary resources, because they would be less likely to experience stresses from poor housing, education, neighborhoods, and communities.…”
Section: Moderating the Effects Of Divorce: Risk And Protective Factorsmentioning
confidence: 99%
“…However, for the majority, the negative effects of divorce, such as unhappiness, distress, depression, alcohol consumption, and health problems, can last 2 to 3 years (Amato, 2000;Hetherington, 2003). Furthermore, for about 10% to 20% of divorced individuals, the negative effects continue or even worsen after 10 years (Duffy, Thomas, & Trayner, 2002;Hetherington, 2003;Perrig-Chiello et al, 2015). Research also suggests that divorce is related to a loss Group Treatment.…”
Section: The Impact Of Divorcementioning
confidence: 99%
“…Moreover, some individuals are exposed to more intense and many secondary stresses after divorce due to demographic and structural features, and therefore, adjustment processes can be more difficult (Amato, 2010;Diedrick, 1991;Williams & Dunne-Bryant, 2006). Relevant studies have revealed that single mothers are more exposed to secondary stress factors associated with the termination of marriage, such as relationships with ex-spouses, relationships with children, financial issues, change in work and living spaces, and social pressure or stigma, and eventually, adjustment may be more difficult (Dahl et al, 2015;Duffy et al, 2002;Hardesty et al, 2019;Holden & Smock, 1991;İlhan, 2020;Konstam et al, 2016;Uyar & Yıldırım, 2022;Williams & Dunne-Bryant, 2006). Having a child is a secondary stress agent in the post-divorce adjustment process whereas having custody of a younger child, who needs more parental care, is considered a situation that makes adjustment more difficult (Williams & Dunne-Bryant, 2006).…”
mentioning
confidence: 99%